JP2013502370A - ダウン・ドロー用ジルコン適合性ガラス - Google Patents
ダウン・ドロー用ジルコン適合性ガラス Download PDFInfo
- Publication number
- JP2013502370A JP2013502370A JP2012525727A JP2012525727A JP2013502370A JP 2013502370 A JP2013502370 A JP 2013502370A JP 2012525727 A JP2012525727 A JP 2012525727A JP 2012525727 A JP2012525727 A JP 2012525727A JP 2013502370 A JP2013502370 A JP 2013502370A
- Authority
- JP
- Japan
- Prior art keywords
- glass
- temperature
- mol
- zircon
- breakdown
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Pending
Links
- 239000011521 glass Substances 0.000 title claims abstract description 126
- 229910052845 zircon Inorganic materials 0.000 title claims abstract description 41
- GFQYVLUOOAAOGM-UHFFFAOYSA-N zirconium(iv) silicate Chemical compound [Zr+4].[O-][Si]([O-])([O-])[O-] GFQYVLUOOAAOGM-UHFFFAOYSA-N 0.000 title claims abstract description 41
- 230000015556 catabolic process Effects 0.000 claims abstract description 35
- 229910004298 SiO 2 Inorganic materials 0.000 claims description 30
- 229910018072 Al 2 O 3 Inorganic materials 0.000 claims description 20
- 150000002500 ions Chemical group 0.000 claims description 10
- 230000004927 fusion Effects 0.000 claims description 5
- 229910052708 sodium Inorganic materials 0.000 claims description 5
- 239000007787 solid Substances 0.000 claims description 3
- 230000006835 compression Effects 0.000 claims 4
- 238000007906 compression Methods 0.000 claims 4
- MCMNRKCIXSYSNV-UHFFFAOYSA-N Zirconium dioxide Chemical compound O=[Zr]=O MCMNRKCIXSYSNV-UHFFFAOYSA-N 0.000 description 54
- 239000000203 mixture Substances 0.000 description 32
- 239000011734 sodium Substances 0.000 description 27
- 238000002844 melting Methods 0.000 description 9
- 230000008018 melting Effects 0.000 description 9
- 238000000034 method Methods 0.000 description 9
- 230000007547 defect Effects 0.000 description 7
- 238000012360 testing method Methods 0.000 description 7
- VYPSYNLAJGMNEJ-UHFFFAOYSA-N Silicium dioxide Chemical compound O=[Si]=O VYPSYNLAJGMNEJ-UHFFFAOYSA-N 0.000 description 6
- 238000005342 ion exchange Methods 0.000 description 6
- 239000002245 particle Substances 0.000 description 6
- 230000006378 damage Effects 0.000 description 5
- 229910021645 metal ion Inorganic materials 0.000 description 5
- BASFCYQUMIYNBI-UHFFFAOYSA-N platinum Chemical compound [Pt] BASFCYQUMIYNBI-UHFFFAOYSA-N 0.000 description 5
- 239000013078 crystal Substances 0.000 description 4
- 238000000635 electron micrograph Methods 0.000 description 4
- 238000003286 fusion draw glass process Methods 0.000 description 4
- 239000007788 liquid Substances 0.000 description 4
- 229910052796 boron Inorganic materials 0.000 description 3
- 239000006025 fining agent Substances 0.000 description 3
- 238000007654 immersion Methods 0.000 description 3
- 238000005259 measurement Methods 0.000 description 3
- 239000000155 melt Substances 0.000 description 3
- 238000010309 melting process Methods 0.000 description 3
- -1 respectively Inorganic materials 0.000 description 3
- 239000000377 silicon dioxide Substances 0.000 description 3
- ZOXJGFHDIHLPTG-UHFFFAOYSA-N Boron Chemical compound [B] ZOXJGFHDIHLPTG-UHFFFAOYSA-N 0.000 description 2
- DGAQECJNVWCQMB-PUAWFVPOSA-M Ilexoside XXIX Chemical compound C[C@@H]1CC[C@@]2(CC[C@@]3(C(=CC[C@H]4[C@]3(CC[C@@H]5[C@@]4(CC[C@@H](C5(C)C)OS(=O)(=O)[O-])C)C)[C@@H]2[C@]1(C)O)C)C(=O)O[C@H]6[C@@H]([C@H]([C@@H]([C@H](O6)CO)O)O)O.[Na+] DGAQECJNVWCQMB-PUAWFVPOSA-M 0.000 description 2
- 229910006404 SnO 2 Inorganic materials 0.000 description 2
- 229910006501 ZrSiO Inorganic materials 0.000 description 2
- 229910000272 alkali metal oxide Inorganic materials 0.000 description 2
- 230000008901 benefit Effects 0.000 description 2
- 230000007423 decrease Effects 0.000 description 2
- 238000003280 down draw process Methods 0.000 description 2
- 230000000694 effects Effects 0.000 description 2
- 230000014509 gene expression Effects 0.000 description 2
- 239000000463 material Substances 0.000 description 2
- 239000006060 molten glass Substances 0.000 description 2
- 229910052697 platinum Inorganic materials 0.000 description 2
- 230000008569 process Effects 0.000 description 2
- 238000012545 processing Methods 0.000 description 2
- 239000000047 product Substances 0.000 description 2
- 150000003839 salts Chemical class 0.000 description 2
- ZLMJMSJWJFRBEC-UHFFFAOYSA-N Potassium Chemical group [K] ZLMJMSJWJFRBEC-UHFFFAOYSA-N 0.000 description 1
- 230000006978 adaptation Effects 0.000 description 1
- 229910001413 alkali metal ion Inorganic materials 0.000 description 1
- 229910000287 alkaline earth metal oxide Inorganic materials 0.000 description 1
- 229910052782 aluminium Inorganic materials 0.000 description 1
- XAGFODPZIPBFFR-UHFFFAOYSA-N aluminium Chemical compound [Al] XAGFODPZIPBFFR-UHFFFAOYSA-N 0.000 description 1
- PNEYBMLMFCGWSK-UHFFFAOYSA-N aluminium oxide Inorganic materials [O-2].[O-2].[O-2].[Al+3].[Al+3] PNEYBMLMFCGWSK-UHFFFAOYSA-N 0.000 description 1
- 238000000137 annealing Methods 0.000 description 1
- 150000001768 cations Chemical class 0.000 description 1
- 238000004140 cleaning Methods 0.000 description 1
- 238000012790 confirmation Methods 0.000 description 1
- 238000010586 diagram Methods 0.000 description 1
- 239000012467 final product Substances 0.000 description 1
- 239000005357 flat glass Substances 0.000 description 1
- 230000004907 flux Effects 0.000 description 1
- 238000007496 glass forming Methods 0.000 description 1
- 229910052736 halogen Inorganic materials 0.000 description 1
- 150000002367 halogens Chemical class 0.000 description 1
- 238000007689 inspection Methods 0.000 description 1
- 238000012417 linear regression Methods 0.000 description 1
- 230000014759 maintenance of location Effects 0.000 description 1
- 238000004519 manufacturing process Methods 0.000 description 1
- 238000012986 modification Methods 0.000 description 1
- 230000004048 modification Effects 0.000 description 1
- 238000001907 polarising light microscopy Methods 0.000 description 1
- 229920001690 polydopamine Polymers 0.000 description 1
- 229910052700 potassium Inorganic materials 0.000 description 1
- 239000011591 potassium Substances 0.000 description 1
- FGIUAXJPYTZDNR-UHFFFAOYSA-N potassium nitrate Chemical compound [K+].[O-][N+]([O-])=O FGIUAXJPYTZDNR-UHFFFAOYSA-N 0.000 description 1
- 230000002035 prolonged effect Effects 0.000 description 1
- 230000009467 reduction Effects 0.000 description 1
- 239000011819 refractory material Substances 0.000 description 1
- 238000004626 scanning electron microscopy Methods 0.000 description 1
- 238000012216 screening Methods 0.000 description 1
- 238000003283 slot draw process Methods 0.000 description 1
- 238000010998 test method Methods 0.000 description 1
Images
Classifications
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C3/00—Glass compositions
- C03C3/04—Glass compositions containing silica
- C03C3/076—Glass compositions containing silica with 40% to 90% silica, by weight
- C03C3/083—Glass compositions containing silica with 40% to 90% silica, by weight containing aluminium oxide or an iron compound
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03B—MANUFACTURE, SHAPING, OR SUPPLEMENTARY PROCESSES
- C03B17/00—Forming molten glass by flowing-out, pushing-out, extruding or drawing downwardly or laterally from forming slits or by overflowing over lips
- C03B17/06—Forming glass sheets
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03B—MANUFACTURE, SHAPING, OR SUPPLEMENTARY PROCESSES
- C03B17/00—Forming molten glass by flowing-out, pushing-out, extruding or drawing downwardly or laterally from forming slits or by overflowing over lips
- C03B17/06—Forming glass sheets
- C03B17/064—Forming glass sheets by the overflow downdraw fusion process; Isopipes therefor
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C21/00—Treatment of glass, not in the form of fibres or filaments, by diffusing ions or metals in the surface
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C21/00—Treatment of glass, not in the form of fibres or filaments, by diffusing ions or metals in the surface
- C03C21/001—Treatment of glass, not in the form of fibres or filaments, by diffusing ions or metals in the surface in liquid phase, e.g. molten salts, solutions
- C03C21/002—Treatment of glass, not in the form of fibres or filaments, by diffusing ions or metals in the surface in liquid phase, e.g. molten salts, solutions to perform ion-exchange between alkali ions
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C3/00—Glass compositions
- C03C3/04—Glass compositions containing silica
- C03C3/076—Glass compositions containing silica with 40% to 90% silica, by weight
- C03C3/083—Glass compositions containing silica with 40% to 90% silica, by weight containing aluminium oxide or an iron compound
- C03C3/085—Glass compositions containing silica with 40% to 90% silica, by weight containing aluminium oxide or an iron compound containing an oxide of a divalent metal
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C3/00—Glass compositions
- C03C3/04—Glass compositions containing silica
- C03C3/076—Glass compositions containing silica with 40% to 90% silica, by weight
- C03C3/083—Glass compositions containing silica with 40% to 90% silica, by weight containing aluminium oxide or an iron compound
- C03C3/085—Glass compositions containing silica with 40% to 90% silica, by weight containing aluminium oxide or an iron compound containing an oxide of a divalent metal
- C03C3/087—Glass compositions containing silica with 40% to 90% silica, by weight containing aluminium oxide or an iron compound containing an oxide of a divalent metal containing calcium oxide, e.g. common sheet or container glass
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C3/00—Glass compositions
- C03C3/04—Glass compositions containing silica
- C03C3/076—Glass compositions containing silica with 40% to 90% silica, by weight
- C03C3/089—Glass compositions containing silica with 40% to 90% silica, by weight containing boron
- C03C3/091—Glass compositions containing silica with 40% to 90% silica, by weight containing boron containing aluminium
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C3/00—Glass compositions
- C03C3/04—Glass compositions containing silica
- C03C3/076—Glass compositions containing silica with 40% to 90% silica, by weight
- C03C3/089—Glass compositions containing silica with 40% to 90% silica, by weight containing boron
- C03C3/091—Glass compositions containing silica with 40% to 90% silica, by weight containing boron containing aluminium
- C03C3/093—Glass compositions containing silica with 40% to 90% silica, by weight containing boron containing aluminium containing zinc or zirconium
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C4/00—Compositions for glass with special properties
- C03C4/18—Compositions for glass with special properties for ion-sensitive glass
-
- C—CHEMISTRY; METALLURGY
- C03—GLASS; MINERAL OR SLAG WOOL
- C03C—CHEMICAL COMPOSITION OF GLASSES, GLAZES OR VITREOUS ENAMELS; SURFACE TREATMENT OF GLASS; SURFACE TREATMENT OF FIBRES OR FILAMENTS MADE FROM GLASS, MINERALS OR SLAGS; JOINING GLASS TO GLASS OR OTHER MATERIALS
- C03C2204/00—Glasses, glazes or enamels with special properties
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y10—TECHNICAL SUBJECTS COVERED BY FORMER USPC
- Y10T—TECHNICAL SUBJECTS COVERED BY FORMER US CLASSIFICATION
- Y10T428/00—Stock material or miscellaneous articles
- Y10T428/31—Surface property or characteristic of web, sheet or block
- Y10T428/315—Surface modified glass [e.g., tempered, strengthened, etc.]
Landscapes
- Chemical & Material Sciences (AREA)
- Engineering & Computer Science (AREA)
- Materials Engineering (AREA)
- Organic Chemistry (AREA)
- Life Sciences & Earth Sciences (AREA)
- Chemical Kinetics & Catalysis (AREA)
- General Chemical & Material Sciences (AREA)
- Geochemistry & Mineralogy (AREA)
- Glass Compositions (AREA)
- Surface Treatment Of Glass (AREA)
- Organic Low-Molecular-Weight Compounds And Preparation Thereof (AREA)
- Re-Forming, After-Treatment, Cutting And Transporting Of Glass Products (AREA)
Applications Claiming Priority (3)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| US23576209P | 2009-08-21 | 2009-08-21 | |
| US61/235,762 | 2009-08-21 | ||
| PCT/US2010/046153 WO2011022639A2 (en) | 2009-08-21 | 2010-08-20 | Zircon compatible glasses for down draw |
Related Child Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2015134302A Division JP6240120B2 (ja) | 2009-08-21 | 2015-07-03 | ダウン・ドロー用ジルコン適合性ガラス |
Publications (1)
| Publication Number | Publication Date |
|---|---|
| JP2013502370A true JP2013502370A (ja) | 2013-01-24 |
Family
ID=43605817
Family Applications (2)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2012525727A Pending JP2013502370A (ja) | 2009-08-21 | 2010-08-20 | ダウン・ドロー用ジルコン適合性ガラス |
| JP2015134302A Expired - Fee Related JP6240120B2 (ja) | 2009-08-21 | 2015-07-03 | ダウン・ドロー用ジルコン適合性ガラス |
Family Applications After (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2015134302A Expired - Fee Related JP6240120B2 (ja) | 2009-08-21 | 2015-07-03 | ダウン・ドロー用ジルコン適合性ガラス |
Country Status (9)
| Country | Link |
|---|---|
| US (2) | US8802581B2 (enExample) |
| EP (1) | EP2467339B1 (enExample) |
| JP (2) | JP2013502370A (enExample) |
| KR (1) | KR101831996B1 (enExample) |
| CN (1) | CN102741176B (enExample) |
| BR (1) | BR112012003832A2 (enExample) |
| IN (1) | IN2012DN01534A (enExample) |
| TW (1) | TWI561480B (enExample) |
| WO (1) | WO2011022639A2 (enExample) |
Cited By (8)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2012180270A (ja) * | 2010-05-19 | 2012-09-20 | Asahi Glass Co Ltd | 化学強化用ガラスおよびディスプレイ装置用ガラス板 |
| JPWO2011152414A1 (ja) * | 2010-06-03 | 2013-08-01 | 旭硝子株式会社 | ガラス基板およびその製造方法 |
| KR20150113031A (ko) * | 2013-01-31 | 2015-10-07 | 코닝 인코포레이티드 | 가상 유리 및 이의 제조방법 |
| JP2018532683A (ja) * | 2015-10-22 | 2018-11-08 | コーニング インコーポレイテッド | 高透過率ガラス |
| JP2019512444A (ja) * | 2016-03-04 | 2019-05-16 | コーニング インコーポレイテッド | 表面圧縮応力が高いイオン交換可能なガラス |
| JP2020536036A (ja) * | 2017-10-03 | 2020-12-10 | コーニング インコーポレイテッド | 亀裂抵抗応力プロファイルを有するガラス系物品 |
| JP2021503429A (ja) * | 2017-11-17 | 2021-02-12 | コーニング インコーポレイテッド | 熱履歴の影響を受けにくいアルカリ含有ガラス |
| WO2021171761A1 (ja) * | 2020-02-25 | 2021-09-02 | 日本電気硝子株式会社 | 強化ガラス板及び強化用ガラス板 |
Families Citing this family (126)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2716848B2 (ja) | 1990-07-17 | 1998-02-18 | 新日本製鐵株式会社 | 低水素系被覆アーク溶接棒 |
| JP2011505323A (ja) | 2007-11-29 | 2011-02-24 | コーニング インコーポレイテッド | 改良された強靭性および引っかき抵抗性を有するガラス |
| US8647995B2 (en) | 2009-07-24 | 2014-02-11 | Corsam Technologies Llc | Fusion formable silica and sodium containing glasses |
| US8802581B2 (en) * | 2009-08-21 | 2014-08-12 | Corning Incorporated | Zircon compatible glasses for down draw |
| US10421681B2 (en) | 2010-07-12 | 2019-09-24 | Corning Incorporated | Alumina isopipes for use with tin-containing glasses |
| TWI537231B (zh) | 2010-07-12 | 2016-06-11 | 康寧公司 | 高靜態疲勞的氧化鋁隔離管 |
| US9434644B2 (en) * | 2010-09-30 | 2016-09-06 | Avanstrate Inc. | Cover glass and method for producing cover glass |
| JP5612233B1 (ja) * | 2010-12-24 | 2014-10-22 | 旭硝子株式会社 | 化学強化用ガラス |
| JP5834793B2 (ja) * | 2010-12-24 | 2015-12-24 | 旭硝子株式会社 | 化学強化ガラスの製造方法 |
| MY187208A (en) | 2011-03-11 | 2021-09-10 | Saint Gobain Ceramics | Refractory object, glass overflow forming block, and process for glass object manufacture |
| RU2570213C2 (ru) | 2011-03-30 | 2015-12-10 | Сэнт-Гобэн Керамикс Энд Пластикс, Инк. | Огнеупорное изделие и способ его формования и использования |
| EP2697177B1 (en) | 2011-04-13 | 2020-11-18 | Saint-Gobain Ceramics & Plastics, Inc. | Refractory object including beta alumina and processes of making and using the same |
| US9783452B2 (en) | 2011-07-01 | 2017-10-10 | Corning Incorporated | Ion-exchanged glass of high surface compression and shallow depth of layer with high resistance to radial crack formation from vickers indentation |
| US10350139B2 (en) | 2011-10-25 | 2019-07-16 | Corning Incorporated | Pharmaceutical glass packaging assuring pharmaceutical sterility |
| US9186295B2 (en) | 2011-10-25 | 2015-11-17 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9517966B2 (en) | 2011-10-25 | 2016-12-13 | Corning Incorporated | Glass compositions with improved chemical and mechanical durability |
| US8556637B2 (en) | 2011-10-25 | 2013-10-15 | Corning Incorporated | Method and apparatus for forming a writable erasable area on an object |
| AU2012328981B2 (en) | 2011-10-25 | 2016-07-07 | Corning Incorporated | Alkaline earth alumino-silicate glass compositions with improved chemical and mechanical durability |
| SG10201809231TA (en) * | 2011-10-25 | 2018-11-29 | Corning Inc | Glass compositions with improved chemical and mechanical durability |
| CN104114503A (zh) | 2011-11-16 | 2014-10-22 | 康宁股份有限公司 | 具有高裂纹引发阈值的可离子交换玻璃 |
| TWI597254B (zh) | 2012-01-11 | 2017-09-01 | 聖高拜陶器塑膠公司 | 耐火物件 |
| WO2013116420A1 (en) * | 2012-02-01 | 2013-08-08 | Corning Incorporated | Method of producing constancy of compressive stress in glass in an ion-exchange process |
| US9359251B2 (en) | 2012-02-29 | 2016-06-07 | Corning Incorporated | Ion exchanged glasses via non-error function compressive stress profiles |
| US8746010B2 (en) * | 2012-03-12 | 2014-06-10 | Corning Incorporated | Methods for reducing zirconia defects in glass sheets |
| US20130255314A1 (en) * | 2012-03-27 | 2013-10-03 | Douglas C. Allan | Method for fusion drawing ion-exchangeable glass |
| TWI593644B (zh) | 2012-05-09 | 2017-08-01 | 康寧公司 | 製造覆蓋玻璃的方法 |
| EP2855384B1 (en) | 2012-05-29 | 2020-12-09 | Corning Incorporated | Method for texturing a glass surface |
| KR102282976B1 (ko) * | 2012-05-31 | 2021-07-29 | 코닝 인코포레이티드 | 높은 내손상성을 갖는 지르콘 호환가능한, 이온 교환가능한 유리 |
| US9512029B2 (en) | 2012-05-31 | 2016-12-06 | Corning Incorporated | Cover glass article |
| US9145333B1 (en) * | 2012-05-31 | 2015-09-29 | Corning Incorporated | Chemically-strengthened borosilicate glass articles |
| US10898933B2 (en) | 2012-05-31 | 2021-01-26 | Corning Incorporated | Oleophobic glass articles |
| US9517967B2 (en) | 2012-05-31 | 2016-12-13 | Corning Incorporated | Ion exchangeable glass with high damage resistance |
| US10273048B2 (en) | 2012-06-07 | 2019-04-30 | Corning Incorporated | Delamination resistant glass containers with heat-tolerant coatings |
| US9499431B2 (en) | 2012-06-08 | 2016-11-22 | Corning Incorporated | Strengthened glass articles and methods of making |
| JP6168288B2 (ja) * | 2012-06-13 | 2017-07-26 | 日本電気硝子株式会社 | 強化ガラス及び強化ガラス板 |
| CN104302591A (zh) * | 2012-06-25 | 2015-01-21 | 日本电气硝子株式会社 | 强化玻璃基板及其制造方法 |
| US9284218B1 (en) | 2012-06-29 | 2016-03-15 | Corning Incorporated | Methods for chemically strengthening glass articles |
| US9139469B2 (en) | 2012-07-17 | 2015-09-22 | Corning Incorporated | Ion exchangeable Li-containing glass compositions for 3-D forming |
| JP6360055B2 (ja) * | 2012-08-17 | 2018-07-18 | コーニング インコーポレイテッド | 極薄強化ガラス |
| US20140087193A1 (en) * | 2012-09-26 | 2014-03-27 | Jeffrey Scott Cites | Methods for producing ion exchanged glass and resulting apparatus |
| US9387651B2 (en) | 2012-09-26 | 2016-07-12 | Corning Incorporated | Methods for producing ion exchanged glass and resulting apparatus |
| EP2922795A1 (en) | 2012-11-20 | 2015-09-30 | Corning Incorporated | Method of making three dimensional glass ceramic article |
| US20140154661A1 (en) | 2012-11-30 | 2014-06-05 | Corning Incorporated | Durable glass articles for use as writable erasable marker boards |
| US20140152914A1 (en) * | 2012-11-30 | 2014-06-05 | Corning Incorporated | Low-Fe Glass for IR Touch Screen Applications |
| US9266768B2 (en) | 2013-01-21 | 2016-02-23 | Corning Incorporated | High purity nickel molds for optical quality glass forming |
| US9308616B2 (en) | 2013-01-21 | 2016-04-12 | Innovative Finishes LLC | Refurbished component, electronic device including the same, and method of refurbishing a component of an electronic device |
| WO2014120641A2 (en) * | 2013-01-31 | 2014-08-07 | Corning Incorporated | Transition metal-containing, ion exchangeable colored glasses |
| KR102169675B1 (ko) | 2013-02-15 | 2020-10-26 | 코닝 인코포레이티드 | 낮은 지르코니아 수준을 갖는 디스플레이 품질 유리 시트의 대량 생산 |
| WO2014133932A1 (en) | 2013-02-26 | 2014-09-04 | Corning Incorporated | Decorative porous inorganic layer compatible with ion exchange processes |
| US9839579B2 (en) | 2013-04-24 | 2017-12-12 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9717648B2 (en) | 2013-04-24 | 2017-08-01 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9707155B2 (en) | 2013-04-24 | 2017-07-18 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9603775B2 (en) | 2013-04-24 | 2017-03-28 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9707153B2 (en) | 2013-04-24 | 2017-07-18 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9700486B2 (en) | 2013-04-24 | 2017-07-11 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9849066B2 (en) | 2013-04-24 | 2017-12-26 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9713572B2 (en) | 2013-04-24 | 2017-07-25 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9700485B2 (en) | 2013-04-24 | 2017-07-11 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9717649B2 (en) | 2013-04-24 | 2017-08-01 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| US9707154B2 (en) | 2013-04-24 | 2017-07-18 | Corning Incorporated | Delamination resistant pharmaceutical glass containers containing active pharmaceutical ingredients |
| CN105121371A (zh) * | 2013-04-29 | 2015-12-02 | 康宁公司 | 光伏模块封装 |
| TWI631049B (zh) | 2013-05-07 | 2018-08-01 | Corning Incorporated | 製造3d玻璃蓋的方法以及用於估計3d玻璃蓋的形狀之電腦實施方法 |
| WO2014182553A1 (en) | 2013-05-07 | 2014-11-13 | Corning Incorporated | Process and apparatus for forming shaped glass articles |
| US11079309B2 (en) | 2013-07-26 | 2021-08-03 | Corning Incorporated | Strengthened glass articles having improved survivability |
| US9790128B2 (en) | 2013-08-07 | 2017-10-17 | Corning Incorporated | Laser controlled ion exchange process and glass articles formed therefrom |
| CN113860730A (zh) * | 2013-08-27 | 2021-12-31 | 康宁股份有限公司 | 具有高热膨胀系数的耐损坏的玻璃 |
| CN105683116A (zh) | 2013-08-30 | 2016-06-15 | 康宁股份有限公司 | 低反射率制品及其制造方法 |
| JP6392363B2 (ja) | 2013-10-14 | 2018-09-19 | コーニング インコーポレイテッド | イオン交換プロセスおよびそれにより得られる化学強化されたガラス基材 |
| DE102013019003A1 (de) * | 2013-11-13 | 2015-05-13 | Taiwan Glass Ind. Corp. | Alkali-Alumino-Silikatglas |
| KR102314817B1 (ko) * | 2013-11-19 | 2021-10-20 | 코닝 인코포레이티드 | 이온 교환 가능한 높은 내손상성 유리 |
| JP2016537290A (ja) * | 2013-11-26 | 2016-12-01 | コーニング インコーポレイテッド | 押込み閾値の高い高速イオン交換可能なガラス |
| US10118858B2 (en) | 2014-02-24 | 2018-11-06 | Corning Incorporated | Strengthened glass with deep depth of compression |
| JP6630287B2 (ja) | 2014-03-27 | 2020-01-15 | コーニング インコーポレイテッド | ガラス物品 |
| JP6697399B2 (ja) | 2014-05-07 | 2020-05-20 | コーニング インコーポレイテッド | 積層ガラス物品及びその形成方法 |
| US9670088B2 (en) | 2014-05-20 | 2017-06-06 | Corning Incorporated | Scratch resistant glass and method of making |
| WO2015186486A1 (ja) * | 2014-06-04 | 2015-12-10 | 旭硝子株式会社 | 導光板用のガラス板 |
| TWI852054B (zh) | 2014-06-19 | 2024-08-11 | 美商康寧公司 | 無易碎應力分布曲線的玻璃 |
| JP2017530383A (ja) | 2014-07-30 | 2017-10-12 | コーニング インコーポレイテッド | 高コントラストの、ガラスに基づく書込み可能/消去可能な前面投影スクリーン |
| US10611664B2 (en) | 2014-07-31 | 2020-04-07 | Corning Incorporated | Thermally strengthened architectural glass and related systems and methods |
| US20160031752A1 (en) | 2014-07-31 | 2016-02-04 | Corning Incorporated | Glass or glass-ceramic for windows, countertops, and other applications |
| US11097974B2 (en) | 2014-07-31 | 2021-08-24 | Corning Incorporated | Thermally strengthened consumer electronic glass and related systems and methods |
| KR102584492B1 (ko) | 2014-10-08 | 2023-10-04 | 코닝 인코포레이티드 | 금속 산화물 농도 구배를 포함한 유리 및 유리 세라믹 |
| US10150698B2 (en) | 2014-10-31 | 2018-12-11 | Corning Incorporated | Strengthened glass with ultra deep depth of compression |
| EP4011843A3 (en) | 2014-11-04 | 2022-06-29 | Corning Incorporated | Deep non-frangible stress profiles and methods of making |
| EP3262011A4 (en) | 2015-02-24 | 2018-08-01 | Saint-Gobain Ceramics&Plastics, Inc. | Refractory article and method of making |
| TWI687375B (zh) | 2015-03-20 | 2020-03-11 | 美商康寧公司 | 用於成形基於玻璃的材料之模具與製作該模具之方法 |
| WO2016176096A1 (en) | 2015-04-30 | 2016-11-03 | Corning Incorporated | Electrically conductive articles with discrete metallic silver layers and methods for making same |
| US11613103B2 (en) | 2015-07-21 | 2023-03-28 | Corning Incorporated | Glass articles exhibiting improved fracture performance |
| US10579106B2 (en) | 2015-07-21 | 2020-03-03 | Corning Incorporated | Glass articles exhibiting improved fracture performance |
| US12338159B2 (en) | 2015-07-30 | 2025-06-24 | Corning Incorporated | Thermally strengthened consumer electronic glass and related systems and methods |
| US10351459B2 (en) | 2015-08-14 | 2019-07-16 | Corning Incorporated | Molds and methods to control mold surface quality |
| WO2017087204A1 (en) | 2015-11-18 | 2017-05-26 | Corning Incorporated | Powder, process of making the powder, and articles made therefrom |
| CN108290775A (zh) | 2015-11-23 | 2018-07-17 | 康宁股份有限公司 | 从玻璃基材去除无机涂层 |
| DK3386930T3 (da) | 2015-12-11 | 2021-07-26 | Corning Inc | Fusionsformbare, glasbaserede artikler indbefattende en metaloxidkoncentrationsgradient |
| US20190256406A1 (en) | 2015-12-16 | 2019-08-22 | Corning Incorporated | Decorative non-porous layers for ion-exchangeable glass substrates |
| CN108367965A (zh) | 2015-12-17 | 2018-08-03 | 康宁股份有限公司 | 具有快速扩散性的可进行离子交换的玻璃 |
| KR102492060B1 (ko) | 2016-01-12 | 2023-01-26 | 코닝 인코포레이티드 | 얇은, 열적 및 화학적으로 강화된 유리-계 제품 |
| CN113800783A (zh) | 2016-01-21 | 2021-12-17 | Agc株式会社 | 化学强化玻璃以及化学强化用玻璃 |
| EP3904302A1 (en) | 2016-04-08 | 2021-11-03 | Corning Incorporated | Glass-based articles including a metal oxide concentration gradient |
| KR102962602B1 (ko) | 2016-04-08 | 2026-05-08 | 코닝 인코포레이티드 | 두 영역을 포함하는 응력 프로파일을 포함하는 유리-계 물품, 및 제조 방법 |
| KR102710638B1 (ko) | 2017-02-02 | 2024-09-27 | 코닝 인코포레이티드 | 유리 표면 가까이에 변경된 k2o 프로파일을 갖는 리튬 함유 유리 또는 유리 세라믹 물품 |
| KR102590179B1 (ko) * | 2017-03-31 | 2023-10-19 | 코닝 인코포레이티드 | 고투과율 유리 |
| TWI766041B (zh) * | 2017-06-14 | 2022-06-01 | 美商康寧公司 | 控制壓實的方法 |
| WO2019040818A2 (en) | 2017-08-24 | 2019-02-28 | Corning Incorporated | GLASSES HAVING ENHANCED TEMPERATURE CAPABILITIES |
| NL2020896B1 (en) | 2018-05-08 | 2019-11-14 | Corning Inc | Water-containing glass-based articles with high indentation cracking threshold |
| TWI785156B (zh) | 2017-11-30 | 2022-12-01 | 美商康寧公司 | 具有高熱膨脹係數及對於熱回火之優先破裂行為的非離子交換玻璃 |
| GB201806356D0 (en) * | 2018-04-18 | 2018-05-30 | Alzahrani Ali Saleh A | Chemically strengthened glass-ceramics |
| CN108975693B (zh) * | 2018-07-02 | 2021-04-16 | 芜湖东旭光电装备技术有限公司 | 玻璃组合物以及耐刮擦玻璃及其制备方法和应用 |
| WO2020046730A1 (en) | 2018-08-30 | 2020-03-05 | Corning Incorporated | Soft, chemically-strengthenable glasses for laminates |
| US12037282B2 (en) | 2018-11-01 | 2024-07-16 | Corning Incorporated | Strengthened glass articles with reduced delayed breakage and methods of making the same |
| TWI891613B (zh) | 2018-11-16 | 2025-08-01 | 美商康寧公司 | 用於透過蒸氣處理而強化之玻璃成分及方法 |
| KR102687909B1 (ko) | 2019-04-16 | 2024-07-24 | 코닝 인코포레이티드 | 이온 교환을 위한 기공-충전된 장식층 및 자동차용 유리 |
| KR20210154825A (ko) | 2019-04-23 | 2021-12-21 | 코닝 인코포레이티드 | 확정 응력 프로파일을 갖는 유리 라미네이트 및 그 제조방법 |
| US20220234947A1 (en) | 2019-05-14 | 2022-07-28 | Corning Incorporated | A 3d structure for easy-to-clean coatings |
| WO2020231959A1 (en) | 2019-05-16 | 2020-11-19 | Corning Incorporated | Glasses with modified young's modulus profile |
| US12122711B2 (en) | 2019-05-16 | 2024-10-22 | Corning Incorporated | Steam strengthenable glass compositions with low phosphorous content |
| CN114127024B (zh) | 2019-05-16 | 2023-10-24 | 康宁股份有限公司 | 具有蒸汽处理雾度抗性的玻璃组合物及其方法 |
| CN116811379B (zh) | 2019-08-06 | 2026-01-02 | 康宁股份有限公司 | 具有用于阻止裂纹的埋入式应力尖峰的玻璃层压体及其制造方法 |
| KR102810414B1 (ko) | 2019-08-29 | 2025-05-21 | 코닝 인코포레이티드 | 초-박형 유리를 위한 이온 교환 공정 |
| DE102019217977A1 (de) * | 2019-11-21 | 2021-05-27 | Schott Ag | Glas, Verfahren zur Herstellung eines Glases und Glasschmelzanlage |
| US12084381B2 (en) | 2019-12-13 | 2024-09-10 | Corning Incorporated | Low-modulus ion-exchangeable glasses |
| GB202012825D0 (en) | 2020-05-12 | 2020-09-30 | Corning Inc | Fusion formable and steam strengthenable glass compositions with platinum compatibility |
| WO2022169701A1 (en) | 2021-02-04 | 2022-08-11 | Corning Incorporated | Low-modulus ion-exchangeable glasses for enhanced manufacturability |
| US20250187971A1 (en) * | 2022-03-09 | 2025-06-12 | Corning Incorporated | Boroaluminosilicate glass composition having high fusion flow rate and advantaged pair shaping temperature |
| DE102023113419B3 (de) * | 2023-05-23 | 2024-08-01 | Schott Ag | Verbundglas, insbesondere für ein Fahrzeug |
| WO2026072479A1 (en) | 2024-09-26 | 2026-04-02 | Corning Incorporated | Strengthened glass articles with deep outer compression from ion exchange on cylindrically thermally induced bending stress profile |
Citations (8)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPH03237036A (ja) * | 1989-08-24 | 1991-10-22 | Nippon Electric Glass Co Ltd | アルミナパッケージ用薄板状硼けい酸ガラス |
| JPH10197485A (ja) * | 1996-09-03 | 1998-07-31 | Hewlett Packard Co <Hp> | 電子捕獲型検出器 |
| JP2002358626A (ja) * | 2001-05-31 | 2002-12-13 | Hoya Corp | 情報記録媒体用ガラス基板及びそれを用いた磁気情報記録媒体 |
| WO2008143999A1 (en) * | 2007-05-18 | 2008-11-27 | Corning Incorporated | Down-drawable, chemically strengthened glass for cover plate |
| JP2009057271A (ja) * | 2007-08-03 | 2009-03-19 | Nippon Electric Glass Co Ltd | 強化ガラス基板及びその製造方法 |
| JP2009084075A (ja) * | 2007-09-27 | 2009-04-23 | Nippon Electric Glass Co Ltd | 強化ガラス基板及びガラス並びに強化ガラス基板の製造方法 |
| JP2009084076A (ja) * | 2007-09-27 | 2009-04-23 | Nippon Electric Glass Co Ltd | 強化ガラス及び強化ガラス基板、並びにその製造方法 |
| US20090142568A1 (en) * | 2007-11-29 | 2009-06-04 | Matthew John Dejneka | Glasses having improved toughness and scratch resistance |
Family Cites Families (28)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| US3844801A (en) * | 1971-02-08 | 1974-10-29 | Owens Corning Fiberglass Corp | Cladding glass compositions for light transmitting glass fibers |
| US3811853A (en) * | 1972-05-01 | 1974-05-21 | Corning Glass Works | Degradable glass suitable for containers |
| JPH01226749A (ja) | 1988-03-08 | 1989-09-11 | Ngk Insulators Ltd | セラミック接合ガラス組成物 |
| US6818573B2 (en) | 1994-05-31 | 2004-11-16 | Tec Ventures, Inc. | Method for molding dental restorations and related apparatus |
| WO1996024560A1 (en) * | 1995-02-10 | 1996-08-15 | Asahi Glass Company Ltd. | Scratch-resistant glass |
| US6119483A (en) * | 1996-12-30 | 2000-09-19 | Hoya Corporation | Process for producing glass substrate for information recording medium |
| GB2335423A (en) | 1998-03-20 | 1999-09-22 | Pilkington Plc | Chemically toughenable glass |
| JPH11310430A (ja) | 1998-04-27 | 1999-11-09 | Asahi Glass Co Ltd | 基板として用いるためのガラス組成物 |
| DE19958517C1 (de) * | 1999-12-04 | 2001-06-21 | Schott Glas | Bleifreie optische Leichtflintgläser |
| WO2001050464A1 (en) | 2000-01-05 | 2001-07-12 | Schott Glass Technologies, Inc. | Glass substrates for magnetic media and magnetic media based on such glass substrates |
| DE10064808B4 (de) | 2000-12-22 | 2005-09-01 | Schott Ag | Zinkoxidhaltiges Borosilicatglas und dessen Verwendungen |
| DE10133521C1 (de) * | 2001-07-10 | 2002-09-05 | Schott Glas | Bleifreie Optische Gläser |
| DE102004033653B4 (de) * | 2004-07-12 | 2013-09-19 | Schott Ag | Verwendung eines Glases für EEFL Fluoreszenzlampen |
| EP1838633B1 (en) | 2004-12-30 | 2017-05-24 | Corning Incorporated | Refractory materials |
| JPWO2007094373A1 (ja) * | 2006-02-14 | 2009-07-09 | 日本板硝子株式会社 | ガラス組成物 |
| WO2007138986A1 (ja) * | 2006-05-25 | 2007-12-06 | Nippon Electric Glass Co., Ltd. | 強化ガラス及びその製造方法 |
| EP2036867B1 (en) * | 2006-06-08 | 2016-10-05 | Hoya Corporation | Glass for use as substrate for information recording medium, substrate for information recording medium, information recording medium, and their production methods |
| EP2075237B1 (en) * | 2006-10-10 | 2019-02-27 | Nippon Electric Glass Co., Ltd. | Reinforced glass substrate |
| JP4819669B2 (ja) | 2006-12-28 | 2011-11-24 | 株式会社日立製作所 | リプレース提案システム |
| JP2008195602A (ja) * | 2007-01-16 | 2008-08-28 | Nippon Electric Glass Co Ltd | 強化ガラス基板の製造方法及び強化ガラス基板 |
| EP2134660B1 (en) * | 2007-03-28 | 2016-11-02 | Pilkington Group Limited | Glass composition |
| CN101679105B (zh) * | 2007-06-07 | 2015-06-17 | 日本电气硝子株式会社 | 强化玻璃基板及其制造方法 |
| EP2252558A4 (en) * | 2008-02-08 | 2014-08-27 | Corning Inc | DAMAGING RESISTANT, CHEMICALLY PREVENTED PROTECTIVE GLASS |
| DE202009018732U1 (de) * | 2008-02-26 | 2013-01-17 | Corning Inc. | Läutermittel für Silikatgläser |
| US8232218B2 (en) * | 2008-02-29 | 2012-07-31 | Corning Incorporated | Ion exchanged, fast cooled glasses |
| WO2010005578A1 (en) * | 2008-07-11 | 2010-01-14 | Corning Incorporated | Glass with compressive surface for consumer applications |
| US8187987B2 (en) * | 2008-08-21 | 2012-05-29 | Corning Incorporated | Durable glass housings/enclosures for electronic devices |
| US8802581B2 (en) * | 2009-08-21 | 2014-08-12 | Corning Incorporated | Zircon compatible glasses for down draw |
-
2010
- 2010-08-16 US US12/856,840 patent/US8802581B2/en active Active
- 2010-08-19 TW TW099127635A patent/TWI561480B/zh not_active IP Right Cessation
- 2010-08-20 IN IN1534DEN2012 patent/IN2012DN01534A/en unknown
- 2010-08-20 EP EP10748026.1A patent/EP2467339B1/en not_active Not-in-force
- 2010-08-20 CN CN201080044762.1A patent/CN102741176B/zh active Active
- 2010-08-20 JP JP2012525727A patent/JP2013502370A/ja active Pending
- 2010-08-20 KR KR1020127007361A patent/KR101831996B1/ko active Active
- 2010-08-20 BR BR112012003832A patent/BR112012003832A2/pt not_active IP Right Cessation
- 2010-08-20 WO PCT/US2010/046153 patent/WO2011022639A2/en not_active Ceased
-
2014
- 2014-08-11 US US14/456,354 patent/US9556058B2/en active Active
-
2015
- 2015-07-03 JP JP2015134302A patent/JP6240120B2/ja not_active Expired - Fee Related
Patent Citations (9)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPH03237036A (ja) * | 1989-08-24 | 1991-10-22 | Nippon Electric Glass Co Ltd | アルミナパッケージ用薄板状硼けい酸ガラス |
| JPH10197485A (ja) * | 1996-09-03 | 1998-07-31 | Hewlett Packard Co <Hp> | 電子捕獲型検出器 |
| JP2002358626A (ja) * | 2001-05-31 | 2002-12-13 | Hoya Corp | 情報記録媒体用ガラス基板及びそれを用いた磁気情報記録媒体 |
| WO2008143999A1 (en) * | 2007-05-18 | 2008-11-27 | Corning Incorporated | Down-drawable, chemically strengthened glass for cover plate |
| JP2009057271A (ja) * | 2007-08-03 | 2009-03-19 | Nippon Electric Glass Co Ltd | 強化ガラス基板及びその製造方法 |
| JP2009084075A (ja) * | 2007-09-27 | 2009-04-23 | Nippon Electric Glass Co Ltd | 強化ガラス基板及びガラス並びに強化ガラス基板の製造方法 |
| JP2009084076A (ja) * | 2007-09-27 | 2009-04-23 | Nippon Electric Glass Co Ltd | 強化ガラス及び強化ガラス基板、並びにその製造方法 |
| US20090142568A1 (en) * | 2007-11-29 | 2009-06-04 | Matthew John Dejneka | Glasses having improved toughness and scratch resistance |
| WO2009070237A1 (en) * | 2007-11-29 | 2009-06-04 | Corning Incorporated | Glasses having improved toughness and scratch resistance |
Cited By (22)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JP2012180270A (ja) * | 2010-05-19 | 2012-09-20 | Asahi Glass Co Ltd | 化学強化用ガラスおよびディスプレイ装置用ガラス板 |
| JPWO2011152414A1 (ja) * | 2010-06-03 | 2013-08-01 | 旭硝子株式会社 | ガラス基板およびその製造方法 |
| KR102302959B1 (ko) * | 2013-01-31 | 2021-09-17 | 코닝 인코포레이티드 | 가상 유리 및 이의 제조방법 |
| KR20150113031A (ko) * | 2013-01-31 | 2015-10-07 | 코닝 인코포레이티드 | 가상 유리 및 이의 제조방법 |
| JP2016504985A (ja) * | 2013-01-31 | 2016-02-18 | コーニング インコーポレイテッド | フィクチベートされた(Fictivated)ガラス及び作製方法 |
| JP2018532683A (ja) * | 2015-10-22 | 2018-11-08 | コーニング インコーポレイテッド | 高透過率ガラス |
| US11242279B2 (en) | 2015-10-22 | 2022-02-08 | Corning Incorporated | High transmission glasses |
| US11186516B2 (en) | 2015-10-22 | 2021-11-30 | Corning Incorporated | Substrates for use in fluorescent-detection methods having glass substrate portion |
| JP2019512444A (ja) * | 2016-03-04 | 2019-05-16 | コーニング インコーポレイテッド | 表面圧縮応力が高いイオン交換可能なガラス |
| US11746045B2 (en) | 2016-03-04 | 2023-09-05 | Corning Incorporated | Ion-exchangeable glass with high surface compressive stress |
| JP7366097B2 (ja) | 2016-03-04 | 2023-10-20 | コーニング インコーポレイテッド | 表面圧縮応力が高いイオン交換可能なガラス |
| JP2022008812A (ja) * | 2016-03-04 | 2022-01-14 | コーニング インコーポレイテッド | 表面圧縮応力が高いイオン交換可能なガラス |
| JP2020536036A (ja) * | 2017-10-03 | 2020-12-10 | コーニング インコーポレイテッド | 亀裂抵抗応力プロファイルを有するガラス系物品 |
| US11523527B2 (en) | 2017-10-03 | 2022-12-06 | Corning Incorporated | Glass-based articles having crack resistant stress profiles |
| JP7361024B2 (ja) | 2017-10-03 | 2023-10-13 | コーニング インコーポレイテッド | 亀裂抵抗応力プロファイルを有するガラス系物品 |
| US11968794B2 (en) | 2017-10-03 | 2024-04-23 | Corning Incorporated | Glass-based articles having crack resistant stress profiles |
| JP2021503429A (ja) * | 2017-11-17 | 2021-02-12 | コーニング インコーポレイテッド | 熱履歴の影響を受けにくいアルカリ含有ガラス |
| JP7386788B2 (ja) | 2017-11-17 | 2023-11-27 | コーニング インコーポレイテッド | 熱履歴の影響を受けにくいアルカリ含有ガラス |
| JPWO2021171761A1 (enExample) * | 2020-02-25 | 2021-09-02 | ||
| WO2021171761A1 (ja) * | 2020-02-25 | 2021-09-02 | 日本電気硝子株式会社 | 強化ガラス板及び強化用ガラス板 |
| US12679759B2 (en) | 2020-02-25 | 2026-07-14 | Nippon Electric Glass Co., Ltd. | Strengthened glass plate and glass plate for strengthening |
| KR102990645B1 (ko) | 2020-02-25 | 2026-07-15 | 니폰 덴키 가라스 가부시키가이샤 | 강화 유리판 및 강화용 유리판 |
Also Published As
| Publication number | Publication date |
|---|---|
| US9556058B2 (en) | 2017-01-31 |
| CN102741176A (zh) | 2012-10-17 |
| US20150024210A1 (en) | 2015-01-22 |
| TW201119956A (en) | 2011-06-16 |
| US8802581B2 (en) | 2014-08-12 |
| KR20120066022A (ko) | 2012-06-21 |
| WO2011022639A2 (en) | 2011-02-24 |
| KR101831996B1 (ko) | 2018-04-04 |
| CN102741176B (zh) | 2015-12-02 |
| WO2011022639A3 (en) | 2011-07-28 |
| IN2012DN01534A (enExample) | 2015-06-05 |
| BR112012003832A2 (pt) | 2017-08-29 |
| EP2467339B1 (en) | 2021-09-15 |
| JP2015205818A (ja) | 2015-11-19 |
| JP6240120B2 (ja) | 2017-11-29 |
| TWI561480B (en) | 2016-12-11 |
| EP2467339A2 (en) | 2012-06-27 |
| US20110045961A1 (en) | 2011-02-24 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| JP6240120B2 (ja) | ダウン・ドロー用ジルコン適合性ガラス | |
| US20240190761A1 (en) | Chemically strengthened glass, method for producing same, and glass for chemical strengthening | |
| KR102659268B1 (ko) | 고 액상선 점도를 갖는 과알루미늄질 리튬 알루미노실리케이트 | |
| JP5444846B2 (ja) | ディスプレイ装置用ガラス板 | |
| TWI647186B (zh) | 在玻璃中達成應力分佈的方法 | |
| TWI639572B (zh) | 具有高熱膨脹係數之抗損壞玻璃 | |
| KR101930681B1 (ko) | 화학 강화용 유리 | |
| JP5416273B2 (ja) | 化学的焼戻しに適したガラスおよび化学的焼戻しされたガラス | |
| KR102217784B1 (ko) | 높은 표면 압축 응력을 가지는 이온 교환 가능 유리 | |
| US12195387B2 (en) | Chemically strengthened glass article and manufacturing method thereof | |
| JP6670462B2 (ja) | 強化ガラス | |
| JP6245275B2 (ja) | 化学強化用ガラス及び化学強化処理されたガラス | |
| JP2011527661A5 (enExample) | ||
| JP2011527661A (ja) | 民生用途のための圧縮面を有するガラス | |
| US20170320769A1 (en) | Glass compositions that retain high compressive stress after post-ion exchange heat treatment | |
| TW201533001A (zh) | 離子可交換的高抗損傷玻璃 | |
| TW201518241A (zh) | 含有硼及磷的可離子交換玻璃 | |
| JP7499180B2 (ja) | 高い破壊靭性を有するガラス | |
| JP2018509366A (ja) | 軟化点が低い、高速イオン交換可能な無ホウ素ガラス | |
| TWI724002B (zh) | 強化玻璃 | |
| JP6022687B2 (ja) | 化学強化用ガラス | |
| KR20260040067A (ko) | 낮은 결정화 경향과 결합된 높은 화학적 강화성을 갖는 유리 및 유리 물품 및 제조 방법 |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| A621 | Written request for application examination |
Free format text: JAPANESE INTERMEDIATE CODE: A621 Effective date: 20130813 |
|
| A977 | Report on retrieval |
Free format text: JAPANESE INTERMEDIATE CODE: A971007 Effective date: 20140218 |
|
| A131 | Notification of reasons for refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A131 Effective date: 20140225 |
|
| A601 | Written request for extension of time |
Free format text: JAPANESE INTERMEDIATE CODE: A601 Effective date: 20140526 |
|
| A602 | Written permission of extension of time |
Free format text: JAPANESE INTERMEDIATE CODE: A602 Effective date: 20140602 |
|
| A601 | Written request for extension of time |
Free format text: JAPANESE INTERMEDIATE CODE: A601 Effective date: 20140625 |
|
| A602 | Written permission of extension of time |
Free format text: JAPANESE INTERMEDIATE CODE: A602 Effective date: 20140702 |
|
| A601 | Written request for extension of time |
Free format text: JAPANESE INTERMEDIATE CODE: A601 Effective date: 20140725 |
|
| A602 | Written permission of extension of time |
Free format text: JAPANESE INTERMEDIATE CODE: A602 Effective date: 20140801 |
|
| A521 | Request for written amendment filed |
Free format text: JAPANESE INTERMEDIATE CODE: A523 Effective date: 20140825 |
|
| A02 | Decision of refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A02 Effective date: 20150303 |